Modelling exchange rates volatility in Latinamerica using EGARCH with points of change - Lagos Cordova, Marcial Javier (2022)
This work aims to investigate whether major political events like corruption scandals, presidential impeachment processes or general elections could be associated to points of structural breaks in the volatility of exchange rates in Latin America. Those break points are endogenously determined using the iterated cumulated sums of squares (ICSS) algorithm proposed by Inclan and Tiao (1994). Since exchange rates are asset prices, finding the effect of shocks in the volatility persistence is important for building accurate asset pricing models. Then, because it better captures asymmetric characteristics of volatility, the EGARCH(1,1) model introduced by Nelson (1991) is used to evaluate whether persistence in volatility is reduced after accounting for those breakpoints.